2010
DOI: 10.1371/journal.pone.0010601
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Atypical Reaction Profiles of Heme Enzymes with a Novel Mechanistic Hypothesis and Kinetic Treatment

Abstract: Many heme enzymes show remarkable versatility and atypical kinetics. The fungal extracellular enzyme chloroperoxidase (CPO) characterizes a variety of one and two electron redox reactions in the presence of hydroperoxides. A structural counterpart, found in mammalian microsomal cytochrome P450 (CYP), uses molecular oxygen plus NADPH for the oxidative metabolism (predominantly hydroxylation) of substrate in conjunction with a redox partner enzyme, cytochrome P450 reductase. In this study, we employ the two abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 23 publications
(19 reference statements)
4
42
0
Order By: Relevance
“…To determine optimal reaction conditions, we varied the pH value of the assay buffer and the concentrations of pyrogallol and hydrogen peroxide. Our observations for free CPO agree well with previous studies [24,29]. Acidic conditions, with pH values in the range of 3.5 to 4.5, and pyrogallol concentrations at approximately 35 mM resulted in optimum catalytic performance.…”
Section: Peroxidation Of Pyrogallol Catalyzed By Free and Sol-gelsupporting
confidence: 91%
See 1 more Smart Citation
“…To determine optimal reaction conditions, we varied the pH value of the assay buffer and the concentrations of pyrogallol and hydrogen peroxide. Our observations for free CPO agree well with previous studies [24,29]. Acidic conditions, with pH values in the range of 3.5 to 4.5, and pyrogallol concentrations at approximately 35 mM resulted in optimum catalytic performance.…”
Section: Peroxidation Of Pyrogallol Catalyzed By Free and Sol-gelsupporting
confidence: 91%
“…The poor quality of the fit shown in Figure 1(b) for the data on sol-gel entrapped CPO might be caused by large data point variations and the limitations of the substrate inhibition model. Manoj et al [29] demonstrated that the substrate inhibition model used here (see (1)) can yield acceptable fits for individual substrate variations, but global fit parameters were shown to be unattainable [29]. For example, the and values of one substrate depended on the concentration of the other cosubstrate.…”
Section: Peroxidation Of Pyrogallol Catalyzed By Free and Sol-gelmentioning
confidence: 92%
“…Recent advances have demonstrated that CYP3A4 cooperativity involves the binding of multiple (at least 2) substrate molecules to the binding pocket and represents a case of true allostery characterized by effector-induced conformational transitions (Davydov and Halpert, 2008). On the basis of the above theory and our results, the differential effects of PXT on the metabolism of MDZ, similar to the effectors of citral, 6-gingerol, and D-limonene (Zhang and Lim, 2008), can be explained by a two-site model (Korzekwa et al, 1998;Domanski et al, 2001) or a multi-site model (Kenworthy et al, 2001;Manoj et al, 2010;Smirnov et al, 2011) of CYP3A4. It can be hypothesized that PXT can bind to one defined site that is also occupied by MDZ in the position required for 4-hydroxylation (or 19-hydroxylation) and that both substrates can displace each other.…”
Section: Discussionsupporting
confidence: 60%
“…However, substrate inhibition of protopine 6-hydroxylase resulting from the elevated cellular pool of protopine or related alkaloids could potentially result in the decreased accumulation of sanguinarine. Substrate inhibition has been reported for salutaridine reductase involved in morphine biosynthesis in opium poppy (35) and is common in mammalian CYPs (36,37).…”
Section: Discussionmentioning
confidence: 99%